Exámen especial a las Cuentas Bancos, Ingresos y Gastos dela congregación Colegio Santa Mariana de Jesús de la ciudad de Quito en el período comprendido del 1 de septiembre del 2014 al 30 de septiembre del 2015 para verificar la utilización y optimización de recursos. - Espinosa Remache, Jessica Gabriela (2016)
The research is centered in the analysis under special consideration of the Congregation College Mariana de Jesus Quito, the accounts of income, expenses and Banks, in order to analyze and verify possible errors that were committed in the processes influencing these items and other difficulties that arise during the review and determine recommendations to enable the institution to rectify these deviations that will not deal with or do not fit within legal rules that govern the period of analysis. The completion of this review was the primary objective of issuing an objective and professional opinion that generate positive changes in the entity; this test was developed under the knowledge acquired in the years of study and under the current regulations that govern the processes of Accounting and Auditing within the Ecuadorian territory. Both business and society need the credibility of its proven results shown in the financial statements so that they demonstrate how well they manage and use resources, seeking to grow or be in a future bankruptcy plans. Accounting in conjunction with the Audit is relevant to the management of various processes within an organization in place and society in general, because with knowledge in these areas we can reach a deep and effective analysis to demonstrate a professional judgment error or omission of administrative, financial and seek solutions based on timely decision making and efficient.